Procedures for chemical fixation in immunohistochemical analyses of PIN proteins regulating polar auxin transport: Relevance to spaceflight experiments. (August 2018) - Kamada, Motoshi; Miyamoto, Kensuke; Oka, Mariko; Uheda, Eiji; Ueda, Junichi; Higashibata, Akira
Abstract: The mechanism by which gravity controls the polar transport of auxin, a plant hormone regulating multiple physiological processes in higher plants, remains unclear, although an important role of PIN proteins as efflux carriers/facilitators in polar auxin transport is suggested. We are going to study the effect of microgravity on the polar transport of auxin, focusing on the cellular localization of its efflux carrier, PsPIN1 in etiolated pea seedlings and ZmPIN1a in etiolated maize seedlings grown under microgravity conditions on the International Space Station (ISS) using immunohistochemical analyses according to space experimental plans (Ueda, 2016). To obtain adequate results regarding the cellular localization of functional proteins, prolonged chemical fixation processes as well as chemical fixatives should be well-matched to the properties of functional proteins as antigens since experimental analyses will be performed on the ground after keeping samples for a long duration on the ISS. As a result of ground verification, clear detection of the cellular localization of PsPIN1 and ZmPIN1a immunohistochemically was successful based on the results of several kinds of chemical fixation tested, even when etiolated pea and maize seedlings were fixed by immersion in chemical fixative for a long duration. The addition of 0.1% (w/v) Nonidet P-40 to chemical fixative composed of 50% (v/v) ethanol and 5% (v/v) acetic acid or that of 50% (v/v) methanol and 5% (v/v) acetic acid has led to a significant improvement in the immunohistochemical detection of PsPIN1 or ZmPIN1a. These chemical fixatives were also shown to be storage-stable for a long time before use. In this study, adequate chemical fixatives and fixation protocols were developed, which can be used to detect localization of PsPIN1 and ZmPIN1a proteins in young etiolated pea and maize seedlings, respectively, using anti PsPIN1 and ZmPIN1a antibodies. These protocols can be used in spaceflight experiments to investigate the effects of the microgravity environment on the ISS on PIN protein localization in pea and maize seedlings.